Biopetrol synthesized from rubber seed oil using zeolite as catalyst:effect of hexane in solvent extraction of rubber seed - Shamugam, Shanker (2012)
Petrol is the most demanding fuel nowadays. Petrol is used especially as a fuel for cars, aircraft and other vehicles. The declining petroleum source that we face today causes the increasing of the petroleum prices all over the world.This problem can be solved by using an alternative source to replace the usual commercial petrol we are using now.This can be done by producing biopetrol or biofuel. Currently, most of the bio-petrol is produced from oils such as the utilization of palm oil for the production of more environmental friendly bio-fuels.The objective of this study is to synthesize biopetrol from fatty acid in rubber seed oil via catalytic cracking using zeolite as catalyst. Extracting rubber seed oil from the rubber seeds,is a favorable method as rubber seed oil contains more fatty acid to be produced into bio-petrol.The rubber seeds are readily available in our country for ages, cheap and help to improve the socioeconomic issues.The rubber seed oil is extracted using the Soxhlet Extraction method.The cleaned shelled and milled rubber seeds are placed into a thimble in the main chamber of the extractor.The solvent,hexane in the receiving flask is left to boil until it vaporizes and condenses filling up the main chamber,extracting the rubber seed oil from the rubber seeds.The catalytic cracking of the mixture of 0.1L of rubber seed oil,20g of catalyst which is in this case zeolite and anti-bumping granule(to assist well distributed boiling)at 300 0C for 45 minutes is to boost up the rate of reaction so that more successful reactions between the reactant particles can occur.The presence of Isooctane in a sample detected using Gas Chromatogram indicating that bio-petrol can be produced. Standards of different ratio mixtures of hexane and Isooctane were used to obtain chromatograms for Isooctane until a calibration curve is plotted from which the Isooctane produced can be determined.The results show that the actual concentration of Isooctane is very high.This could be explained using the cause of interlayer spacing of catalyst structure, larger surface area for reactions to occur,various types of fatty acid mixture present in rubber seed oil,the incorrect chromatogram modifications and also the contamination in rubber seed oil.The volume of solvent used will affect the percentage of concentration of Isooctane in samples obtained.As a conclusion,bio-petrol can be produced from rubber seed oil using zeolite catalyst in the catalytic cracking process.